Engaging with 'English in a Historical Perspective' Through Analysing Texts. Issue 1 (2nd January 2016) - Wyatt, Mark; Constantino, Dorothy; Cox, Corinne; Gilkes, Kristy; Thompson, Serena; Tiller, Rachael
Abstract: Though there is little in the literature on the teaching of the history of English, criticism of textbooks which over-simplify the story as the rise of the standard variety has been more vocal of late. Meanwhile, some academics have argued for focusing teaching on the analysis of texts. This article reports on a unit/module taught at a British university that makes the analysis of texts central to teaching and assessment. It sets out to demonstrate what can be learned from approaching the subject in this way by presenting composite textual analyses created by the first-named author drawing on the work of his co-authors (five of his final-year undergraduate students). This was for two assignments, one focusing on an Early Modern English text and the other a more contemporary piece. A discussion highlights the benefits of making the analysis of texts central to the unit, and considers practical applications for teachers of the subject in other parts of the world.